Produk Pembiayaan Lembaga Keuangan Syariah Berbasis Akad Ijarah - Arik Hermawan (MASADIR: Jurnal Hukum Islam, 2025)
Abstract: The Ijarah contract is one of the primary instruments in Islamic finance that is used for leasing transactions, serving as a Sharia-compliant alternative to conventional lease agreements. Derived from the Arabic word "Ajr" meaning reward or compensation, Ijarah refers to a contract in which the owner of an asset (lessor) transfers the right of use to another party (lessee) for a specified period and price without transferring ownership. This paper explores the theoretical foundation of Ijarah, its legal basis according to Islamic jurisprudence (fiqh), and its application in contemporary Islamic financial institutions, especially Islamic banks. The study also examines the types of Ijarah, such as Ijarah Muntahiyah bi Tamlik (lease ending with ownership), and how they are implemented to comply with the Sharia principles of fairness, transparency, and risk-sharing. Furthermore, this research includes a comparative analysis between Ijarah and conventional leasing, highlighting the ethical and legal distinctions that make Ijarah a more equitable choice in Islamic finance. Previous empirical studies and fatwas from authoritative Islamic financial bodies are reviewed to support the argument. Ultimately, this study concludes that Ijarah is a flexible and ethically sound contract that plays a significant role in the development of Islamic banking and finance systems.